The biological diversity of coronaviruses: where will the new threat come from? - Alexandr Khaitovich; Tatiana Sataieva; Walery Zukow; Veronika Malygina; Lyudmila Shevkoplyas; Tatiana Logadyr; Marina Kirsanova; Irina Andronovskaya; Ekaterina Soroka (Kazimierz Wielki University, 2022)
The recent outbreak of COVID-19 rose a new wave of interest to coronaviruses though the first coronaviruses were discovered in the first half of the XX century. That time coronaviruses were considered as a quite serious veterinary problem but they were not believed to become highly dangerous for humans. However, such ideas were revised in 2002 when SARS-CoV was transferred to human population in the Southeast Asia assumably from the bats, and later in 2012 when natural focus of the MERS-CoV was discovered in the Arabian countries. Due to the increased interest a large number of new Coronaviridae family members was revealed in the first decades of the XXI century. Since then taxonomic structures of coronaviruses underwent significant changes. This review is focused on the need for continued monitoring of the biological diversity of coronaviruses. The structural studies of coronaviruses regardless of the host species may allow us to identify early changes that can affect the evolutionary drift process of a particular HCoV species in volved in viral transmission from bats or birds to humans.